2015
DOI: 10.1007/s00726-015-2047-5
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation in yeast proteins during stationary-phase growth and heat shock

Abstract: Arginine methyltransferases (RMTs) catalyze the methylation of arginine residues on proteins. We examined the effects of log-phase growth, stationary-phase growth, and heat shock on the formation of methylarginines on yeast proteins to determine if the conditions favor a particular type of methylation. Utilizing linear ion trap mass spectrometry, we identify methylarginines in wild-type and RMT deletion yeast strains using secondary product ion scans (MS(3)), and quantify the methylarginines using multiple rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Studies (Herman, 2002; Verghese et al, 2012) have shown that yeast remain in the G1 phase of the cell cycle due to heat shock and stationary-phase status, and the observed ADMA concentration may also reflect the complete protein methylation pattern. The concentration of ADMA decreased by 11-fold during heat shock and the stationary phase compared to log-phase growth of wild-type S. cerevisiae (Lakowski et al, 2015). In human tissues and cells, ADMA is an endogenous competitive inhibitor of NOS that affects NO production and exerts a variety of biological effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies (Herman, 2002; Verghese et al, 2012) have shown that yeast remain in the G1 phase of the cell cycle due to heat shock and stationary-phase status, and the observed ADMA concentration may also reflect the complete protein methylation pattern. The concentration of ADMA decreased by 11-fold during heat shock and the stationary phase compared to log-phase growth of wild-type S. cerevisiae (Lakowski et al, 2015). In human tissues and cells, ADMA is an endogenous competitive inhibitor of NOS that affects NO production and exerts a variety of biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…ADMA is now considered to be a biologically active agent in cardiovascular diseases (CVDs) (Kielstein et al, 2004). Currently, little is known about the role of ADMA in fungi; a decrease in ADMA is only known to affect the growth of Saccharomyces cerevisiae upon heat stress, stationary phase growth, or other stress states (Lakowski et al, 2015). However, the role of ADMA in filamentous fungi has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…An equal amount of crude lysate (277 mg) from each sample was processed. Sample preparation, chromatographic separation, and mass spectrometry analysis were performed according to published methods (Lakowski et al, 2015). Experimenters were blinded during data acquisition.…”
Section: Quantification Of Methylarginines From Crude Lysatesmentioning
confidence: 99%
“…Precipitates were pelleted at 20,000 g in a tabletop microcentrifuge at 4°C for 30 min. The supernatant was discarded, and the remain- and MMA, and 1-5,000 nM for sDMA (Lakowski et al, 2013(Lakowski et al, , 2015.…”
Section: Quantification Of Methylarginines From Crude Lysatesmentioning
confidence: 99%
“…The expression of ADMA in yeast proteins has been demonstrated. Saccharomyces cerevisiae cells in log-phase growth exhibited 11-fold higher ADMA expression than cells of this yeast under heat shock or in a stationary phase [45]. To study whether ADMA is also involved in the inhibition of T. rubrum growth by HaCaT cells, we cocultured HaCaT cells with T. rubrum, not only to assess NOS expression and the NO level but also to measure the ADMA level.…”
Section: Control Group T+hacat Groupmentioning
confidence: 99%